The great American mission : modernization and the construction of an American world order - Ekbladh, David, 1972- (America in the world., 2010)
The Great American Mission traces how America's global modernization efforts during the twentieth century were a means to remake the world in its own image. David Ekbladh shows that the emerging concept of modernization combined existing development ideas from the Depression. He describes how ambitious New Deal programs like the Tennessee Valley Authority became symbols of American liberalism's ability to marshal the social sciences, state planning, civil society, and technology to produce extensive social and economic change. For proponents, it became a valuable weapon to check the influence.